Deodorizing Activity of Hop Bitter Acids and Their Oxidation Products Against Allyl Methyl Sulfide, a Major Contributor to Unpleasant Garlic-Associated Breath and Body Odor - Atsushi Henmi; Tsutomu Sugino; Akira Sasaki; Kenichi Nakamura; Masakuni Okuhara (Cosmetics, 2025)
Garlic is a spice widely used worldwide, but ingestion of garlic can cause unpleasant breath odor that can be offensive in interpersonal interactions. Among several sulfur-containing components of garlic, allyl methyl sulfide is considered the primary causative agent of unpleasant garlic breath and body odor. We discovered that hop cone powder exhibits potent deodorizing activity against allyl methyl sulfide. Oxidation products of the hop bitter acids humulinone and hulupone were detected in a partially purified sample of hop cone powder. Oxidation products of the α-acids cohumulinone and n-humulinone showed approximately 10- and 15-fold stronger deodorizing activity than the parent α-acids, respectively. The deodorizing activity of oxidation products of β-acids was comparable to that of n-humulinone. It is presumed that the oxidation products of hop powder play an important role in the strong deodorizing activity of hop cone powder against allyl methyl sulfide.